Effect of contour-strip cropping of pineapple (Ananas comosus) on rice (Oryza sativa) - sesame (Sesamum indicum) and maize (Zea mays)sesame cropping sequences and their effect on soil properties - SHARMA, N N; SARMA, D; PAUL, S R; DEY, J K; BORA, P; SINGHA, D D (The Indian Journal of Agricultural Sciences, 2013)
A field experiment was conducted at Diphu in the 25% hill slope with average annual rainfall 1 236 mm, to knowthe utility of pineapple, [Ananas comosus (L) Men] as contour crop just above the main crop in increasing the totalproductivity of rice (Oryza sativa L.) - sesame (Sesamum indicum L.) and maize (Zea mays L) - sesame croppingsequences. The rice - sesame sequence when raised with pineapple-contour strip at the top recorded the highest rice-equivalent yield, showing 23% more yield than that without pineapple - contour strip. Rice - equivalent yield obtainedthrough pineapple-contour strip at the top of the main crop and that at the top and bottom were almost identical andstatistically at par. Pineapple-contour strip above the main crop prevented the run-off and loss of nutrients particularly ofNand K, and contributed to higher residual soil pH, organic matter as well as available N and K.